Analysis of Baturagung Reservoir Leaking, Gedangrejo, Gunung Kidul Regency using Digital Outcrop Model Method - Farisan, Ardhan; Bahagiarti, Sari; Nurwantari, Nanda Ajeng; Setyaningrum, Tuti; Rahatmawati, Istiana; Zakaria, Muhammad Faizal; Probowati, Dyah (Jurnal Lingkungan dan Bencana Geologi, 2024)
Water, serving as a vital resource, finds applications in diverse sectors such as agriculture (irrigation), drinking watersupply, flood control, and hydroelectric power generation. On a smaller scale, the construction of "Embung" or smallartificial reservoirs facilitates water storage during the rainy season for subsequent use in the dry season. Within thestudy area, a reservoir constructed in 2018 has never attained full capacity, a circumstance that piqued the author'sinterest. A combined approach utilizing aerial photogrammetry and ground observation is employed for comprehensiveanalysis. Aerial photogrammetry yields an extensive and accurately depicted geometric representation of geologicalstructures. The investigation focuses on the Semilir Formation, a volcanic formation. Findings reveal that the studyarea manifests a division into nine (9) segments discerned from distinct structural trends. These segments are delineatedby eight (8) faults, with the major fault identified as Fault F6. Fault F6 exhibits a prevailing NNE-SSW trend,consistent with the primary fault on the regional geological map. Notably, Fault F6 encompasses a substantial faultzone traversing the Baturagung Reservoir and stands accountable for the reservoir's leakage.